2019
DOI: 10.1016/j.ptsp.2018.05.015
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between hip muscle strength and dynamic knee valgus in asymptomatic females: A systematic review

Abstract: Although the relationship between hip strength and dynamic lower extremity valgus is conflicting, meta-analysis revealed lower extremity dynamic valgus was consistently associated with hip strength in single leg ballistic tasks, but not double leg ballistic or single leg squat tasks. The relationship between hip strength and dynamic lower extremity valgus may be conditional to task demand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 52 publications
2
48
0
3
Order By: Relevance
“…Este resultado denota que a melhora do padrão de movimento pode melhorar o desempenho em testes de salto. Dix et al (2018) fizeram uma revisão sistemática e meta-análise com o objetivo de investigar a relação entre a força muscular do quadril e o valgo dinâmico das extremidades inferiores durante tarefas de movimento em mulheres assintomáticas. Os autores concluíram que embora a relação entre a força do quadril e o valgo dinâmico seja conflitante, a metanálise revelou que o VDJ foi consistentemente associado à força do quadril nas tarefas balísticas de perna única, mas não àquelas de perna dupla ou agachamento unipodal.…”
Section: Discussionunclassified
“…Este resultado denota que a melhora do padrão de movimento pode melhorar o desempenho em testes de salto. Dix et al (2018) fizeram uma revisão sistemática e meta-análise com o objetivo de investigar a relação entre a força muscular do quadril e o valgo dinâmico das extremidades inferiores durante tarefas de movimento em mulheres assintomáticas. Os autores concluíram que embora a relação entre a força do quadril e o valgo dinâmico seja conflitante, a metanálise revelou que o VDJ foi consistentemente associado à força do quadril nas tarefas balísticas de perna única, mas não àquelas de perna dupla ou agachamento unipodal.…”
Section: Discussionunclassified
“…Strong hip and thigh muscles are thought to increase patellar stability by absorbing external hip and knee moments, preventing movement patterns associated with the LPD mechanism of injury (6). In other patient populations, hip muscle weakness has been associated with knee valgus (26), and quadriceps weakness with reduced knee exion on single leg landing (27,28). Higher quadriceps strength is also protects against patellofemoral joint cartilage loss and is associated with less pain and higher physical function, in people with patellofemoral osteoarthritis (29).…”
Section: Interventionmentioning
confidence: 99%
“…Hence, previous studies conducted exercise intervention targeting the kinetic chain of DKV [4]. During closed chain activities, due to the interdependent of joint motions, excessive motions from one joint may overload subsequent tissues in the kinetic chain [5,6]. There are two types of kinetic chains related to DKV, which are top-down (i.e., proximal origins) and bottom-up (i.e., distal origins).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the top-down kinetic chain, the function of muscles and other soft tissues either at the trunk or hip joint may influence the occurrence of altered kinematic patterns at the subsequent distal joints [7]. It was shown that weakness of hip musculature was associated with greater knee valgus during single leg ballistic and single leg squat tasks [6]. Hip and trunk muscle strengthening are commonly recommended to modify lower limb kinematics such as excessive hip medial rotation and adduction during weight-bearing tasks and to treat and prevent injuries at distal joints of lower limbs [8].…”
Section: Introductionmentioning
confidence: 99%